10.36873/jht.v15i2.2166 PP. 102-111 : Alpian, Robekka, Sarinah, Nuwa, Desi Natalia Koroh, Wahyu Supriyati: KUALITAS ARANG AKTIF PADA TIGA JENIS LIMBAH KAYU UNTUK MENINGKATKAN KUALITAS AIR SUMUR BOR (Activated Charcoal Quality in Three Type of Wood Waste to Improve Water Quality) - JHT, Admin (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2020)
Wood processing industry waste consists of waste produced by the plywood industry, sawing and woodworking consisting of ends, blades, peelings, chips and sawdust. The use of wood waste is not utilized by the furniture industry and one of the solutions to its utilization by processing wood waste into activated charcoal. Activated charcoal can be made from all carbon-containing materials both organic and inorganic provided that the material is porous. Bangkirai, Rengas and Sengon wood waste as materials used in this study were carbonized first then activated charcoal. The quality test of activated charcoal carried out includes yield, air content, ash content, volatile matter content, carbon content, absorption of benzene, absorption of iodine and absorption of methylene blue. Overall, the results of testing the quality of activated charcoal did not all meet the requirements of SNI 06-3730-1995. The quality of activated charcoal from Rengas wood has the best quality (>456.59 mg /g) of all needs because the highest iodine absorption capacity according to Kimia Farma (KF) standards requires (> 426.5 mg/g). Rengas wood activated charcoal to bore wells improves the quality of drinking water No. 416/ Menkes / Per/IX /1990 except turbidity. Keywords : Active Charcoal, Bangkirai Wood Waste, Rengas, Sengon, Drilled Well Water.